Maṣlahaḥ Mursalah Dan Penerapannya Dalam Hukum Keluarga - Muh. Adistira Maulidi Hidayat; Usep Saepullah (Minhaj: Jurnal Ilmu Syariah, 2024)
Maṣlahaḥ mursalah is a legal basis used to regulate new issues that are not explicitly mentioned in the Quran and Sunnah. Every regulation established by naṣh or ijma’ is based on the principle of achieving benefits and preventing harm. Therefore, every legal foundation used stems from the interests and benefits of humanity (al-maṣlahah). Maṣlahah relates to the needs of human life, including aspects such as religion, soul, reason, lineage, dignity, and wealth. Therefore, when clear legal rulings are not found in the Quran or Sunah, Islamic law or fiqh can be established by considering maṣlahaḥ. This writing aims to further elaborate on the concept of maṣlahah mursalah, its legal basis, classification, maṣlahah mursalah as a basis for legal legislation, and its application in family law.